Assessing energy rating premiums in the performance of green office buildings in Australia. Issue 4 (1st July 2014) - Tim Dixon, Professor Susan Bright; Dr Peter Mallaburn, Professor; Newell, Graeme; MacFarlane, John; Walker, Roger
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Green office buildings have recently taken on increased significance in institutional property portfolios in Australia and globally. The key issue from an institutional investor perspective is the assessment of whether green office buildings add value. Using an extensive portfolio of green office buildings, the purpose of this paper is to empirically assess the level of energy rating premiums in the property performance of green office buildings in Australia. Design/methodology/approach – Using a portfolio of over 200 green office buildings in Australia benchmarked against a comparable portfolio of non-green office buildings, the level of energy rating premiums in the property performance of green office buildings in Australia is empirically evaluated. Hedonic regression analysis is used to account for differences between specific office buildings and to explicitly identify the "pure" green effect in identifying the level of energy rating premiums in several commercial property performance characteristics (e.g. office value, rent). Findings – The empirical results show the added-value premium of the 5-star National Australian Built Environment Rating Scheme (NABERS) energy rating scheme and the Green Star scheme in the property performance of green office buildings in Australia, including office values and rents. Energy rating premiums for green office buildings are evident at the top energy ratings and energy rating discounts at the lower energy ratings. The added-value "top-end" premium of the 5-star vs 4-star NABERS energy rating category is clearly identified for the various property performance parameters, including office values and rents. Practical implications – This paper empirically determines the presence of energy rating premiums at the top energy ratings in the performance of green office buildings, as well as energy rating discounts at the lower energy ratings. This clearly highlights the added value dimension of energy efficiency in green office buildings and the need for the major office property investors to prioritise the highest energy rating to facilitate additional property performance premiums. This will also see green office buildings become the norm as the market benchmark rather than non-green office buildings. Social implications – This paper highlights energy performance premiums for green office buildings. This fits into the context of sustainability in the property industry and the broader aspects of corporate social responsibility in the property industry. Originality/value – This paper is the first published property research analysis on the detailed determination of energy rating premiums across the energy rating spectrum for green office buildings in Australia. Given the increased focus on energy efficiency and green office buildings, this research enables empirically validated and practical property investment decisions by office property investors regarding the importance of energy efficiency and green office buildings, and the priority to achieve the highest energy rating to maximise property performance premiums in office values and rents.